Terminologia graeco-latina medica pro bakalářské obory Lékařské fakulty MU Gramatická příručka - Pořízková, Kateřina (Masaryk University Press, 2016)
The Grammar Book was written for the first-year students of selected bachelor's programmes of Faculty of Medicine, Masaryk University. It is a reference book for specialized exercise books for learning the Greek-Latin medical terminology The explanation of grammar rules is followed also by declension tables and a list of abbreviations frequently used in prescriptions.